2023
DOI: 10.1101/2023.02.21.528438
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanisms of Nuclear Pore Complex disassembly by the mitotic Polo-Like Kinase 1 (PLK-1) inC. elegansembryos

Abstract: The nuclear envelope, which protects and organizes the interphase genome, is dismantled during mitosis. In the C. elegans zygote, nuclear envelope breakdown (NEBD) of the parental pronuclei is spatially and temporally regulated during mitosis to promote the unification of the parental genomes. During NEBD, Nuclear Pore Complex (NPC) disassembly is critical for rupturing the nuclear permeability barrier and removing the NPCs from the membranes near the centrosomes and between the juxtaposed pronuclei. By combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 96 publications
(185 reference statements)
1
4
0
Order By: Relevance
“…Analysis of these strains by light-microscopy showed that the nuclear shape is altered, beginning at around NEBD, in spd-3(oj35), consistent with the observed changes in ER morphology surrounding the spindle (Figs S7 and 3A). As previously described, we also found that NPP-22 localizes not only to the nuclear envelope but also accumulates in the ER around the centrosomes, the centriculum (Maheshwari et al, 2023;Nkoula et al, 2023). In addition, we observed NPP-22 also localizing to larger structures around the nucleus, which most likely reflect a localization to ER (Fig 4A).…”
Section: Spd-3 Is Important For Er Morphologysupporting
confidence: 87%
See 1 more Smart Citation
“…Analysis of these strains by light-microscopy showed that the nuclear shape is altered, beginning at around NEBD, in spd-3(oj35), consistent with the observed changes in ER morphology surrounding the spindle (Figs S7 and 3A). As previously described, we also found that NPP-22 localizes not only to the nuclear envelope but also accumulates in the ER around the centrosomes, the centriculum (Maheshwari et al, 2023;Nkoula et al, 2023). In addition, we observed NPP-22 also localizing to larger structures around the nucleus, which most likely reflect a localization to ER (Fig 4A).…”
Section: Spd-3 Is Important For Er Morphologysupporting
confidence: 87%
“…PLK-1 is a master regulator in mitosis with multiple important roles to ensure the proper progression through mitosis such as chromosome alignment (Addis Jones et al, 2019), anaphase entry (von Schubert et al, 2015;O'Connor et al, 2015;Jia et al, 2016), and cytokinesis (Burkard et al, 2007;Rezig et al, 2021). In C. elegans PLK-1 was shown to be involved in establishment of polarity (Koch & Rose, 2023), centrosome maturation (Ohta et al, 2021;Nakajo et al, 2022), nuclear lamin disassembly (Velez-Aguilera et al, 2020), and disassembly of the nuclear pore complex (Nkoula et al, 2023). In agreement with the multiple roles of PLK-1, the spd-3(oj35) embryos show a number of defects that could be linked to PLK-1 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, pixel classifiers powered by machine-learning (ML) models such as ilastik can be trained by a user-defined subjective “ground truth” to yield a mask where every pixel in the image is assigned to one of two categories, namely, condensate or background (Figure , Method #4). , The training of pixel classifiers can be convenient and quick. For example, ilastik is the most widely used interactive ML-based bioimage processing software has been used on condensate images, and it can work with as little as seven condensate images in the training dataset …”
Section: Resultsmentioning
confidence: 99%
“…In C. elegans one-cell embryo, the essential mitotic kinases Aurora A (also known as AIR-1 in C. elegans) and Polo-like kinase (PLK-1 in C. elegans) are implicated in NEBD (Portier et al, 2007;Hachet et al, 2007;Rahman et al, 2015;Martino et al, 2017;Velez-Aguilera et al, 2020;Nkoula et al, 2023). Therefore, we decided to explore whether B55 SUR-6 could act upstream of Aurora A or PLK-1 to regulate NEBD.…”
Section: B55 Sur-6 Orchestrates Nebd Without Influencing the Localiza...mentioning
confidence: 99%